Monoclonal Antibodies as Ligands for Purificaion of Rabies virus Proteins from the Brain Tissues of Infected Dogs and Mice (ANTIBODI MONOCLONAL SEBAGAI LIGAND UNTUK PURIFIKASI PROTEIN VIRUS RABIES ASAL JARINGAN OTAK ANJING DAN MENCIT TERINFEKSI) - Astawa, Nyoman Mantik; Kencana, Gusti Ayu Yuniati; Suardana, Ida Bagus (Jurnal Veteriner; Vol 17 No 4 (2016), 2017)
Immunoaffinity chromatography using monoclonal antibodies (mAbs) as ligands has been used topurify rabies virus (RV) individual proteins. In this method, mAbs against RV were firstly purified,coupled to CnBr-agarose resin and used for purification RV individual proteins. Brain tissue homogenatesderived from infected and uninfected dogs and mice were mixed with mAbs-CnBr agarose resin and washedextensivelly phosphate buffered salin (PBS). Following elution and neutralization, purified proteins weredetected by enzyme-linked immunosirbent assay (ELISA) and Western blotting assay. Of the three mAbs(BB5, AE11 and AF6) as ligands, mAb AE11-CnBr agarose resin yielded highest protein levels as comparedto those of mAb BB5-CnBr agarose and mAb AF6-CnBr agarose resins. In Western Blotting assay, thepurified protein appeared to be 65 Kda (glycoprotein) and 38 kDa proteins. In ELISA test, the purifiedproteins reacted with both mAbs and policlonal antibodies (pAbs).
Keywords: CnBr-agarose; rabies virus; protein; purificaion; chromaography